PELAKSANAAN PENDIDIKAN INKLUSI DI TAMAN KANAK-KANAK YAYASAN PENDIDIKAN SOROAKO - Anggraeni, Farida (Pascasarjana Universitas Negeri Makassar, 2016)
Early childhood education had implemented through education pre-school or kindergarten. One of kindergarten which concerned on increasing the quality of early childhood education was kindergarten Education Foundation at Sorowako. kindergarten received all of the employees’s children in the PT. Vale Indonesia tbk. This, there was not selection, so that there were children who accepted special need. Consequently this school should have inclusion education program for them. That’s why, the aims of this research are: (i) to find out the description of how to implement education for special needs students at Kindergarten of Sorowako Education Foundation, (ii) to know supports and inhibiting factors the implementation of inclusion education for the special needs students at Kindergarten of Sorowako Education Foundation. The approach of this research causes study of qualitative research by collecting data with interviews, observations, and documents studies.The results of this study showed that (i) Implementation of inclusion education in TK YPS Lawewu Sorowako. For children who accepted special needs designed by integrate individual learning programs for them. The result of analysis the data showed the appropriate to design of inclusion education. The differences are not significant caps. And (ii) the factor inhibit the implementation of inclusion education in kindergarten YPS Lawewu Sorowako. Was the number of theraphy staff still less than the number of special children. In addition, there were the teacher who could do as an inclusion teacher and regular teacher while the supporting factors were aduquate funding of PT. Vale Indonesia Tbk. And allocation of learning facilities.